THE IMPORTANCE OF GUIDANCE PRESENCE IN FORMING THE CHARACTER OF STUDENTS IN SAINS ISLAMIC BOARDING SCHOOLS TEBUIRENG JOMBANG - Hosna, Rofiatul; Idawati, Khoirotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research study examines the importance of the presence of teachers in shaping the character of students at the Tebuireng Science Islamic Boarding School. The data collected comes from observations and interviews at the location studied. The research findings show the great influence of the presence of a coach on efforts to shape the character of a student in the Islamic boarding school environment. The presence of a coach as a parent and educator in the boarding school can shape the character of students who are independent, disciplined, moralsocially minded, hardworking, and confident. supported by Islamic boarding school programs and curricula, as well as active coordination from all related parties, to create a conceptual and comprehensive system of character education in Islamic boarding schools.